Flatness Based Control Design for Two-Mass System using Induction Motor Drive Fed by Voltage Source Inverter with Ideal Control Performance of Stator Current - Vo, Thanh Ha; Nguyen, Hai Huynh; Do, Phuc Hung; Nguyen, Phung Quang (Old Journal, 2019)
In theoretical researches of the electrical drive system, it is rigidly coupled system, the stiffness coefficient and damping coefficient of the shaft are neglected. However, the electrical drive system with flexible coupling, it is regarded as a two - mass system. This system, the coefficient negatively influences of flexible coupling causing a decrease in the quality of the electrical drive system. The paper presents the results of flatness based control design for two-mass systems using induction motor drive, fed by voltage source inverter with ideal control performance of stator current with the induction motor working in basic speed range and upper field weakening area. The simulation results presented the correctness and effectiveness of control methods is proposed.